Copper Nanoparticles Supported on Nickel Ferrite: Synthesis and Electrocatalytic Activity - Ivanova, N.M.; Vissurkhanova, Y.A.; Soboleva, Ye.A.; Kenzhetaeva, S.O. (Karagandy University of the name of acad. E.A. Buketov, 2024)
Cu(x)/NiFe2O4(y) magnetic composites with different component ratios were prepared by chemical reduction of copper cations in the presence of sonicated nickel ferrite. Separately synthesized Cu and NiFe2O4 nanoparticles, as well as composites of copper particles supported on nickel ferrite, were characterized by X-ray diffraction spectroscopy and scanning electron microscopy. Based on the determination of the specific surface area, the NiFe2O4 sample heat-treated at 500 °C was selected as the support for the catalytically active Cu particles. The electrocatalytic activity of Cu(x)/NiFe2O4(y) composites deposited on a cathode was investigated in the electrohydrogenation of acetophenone (APh). It was shown that the electrocatalytic activity of these composites appears starting from the percentage ratio of their components x:y = 40:60. This was expressed as an increase in the rate of electrocatalytic hydrogenation of APh and its conversion compared to the electrochemical reduction of APh under similar conditions. It was suggested that the slightly lower rate of APh hydrogenation on Cu/NiFe2O4 composites compared to Cu particles is due to the poor electrical conductivity of the nickel ferrite support.
Keywords: copper nanoparticles; chemical reduction; nickel ferrite carrier; co-precipitation method; catalysts; electrocatalytic hydrogenation; acetophenone; 1-phenylethanol